2005
DOI: 10.1080/01411590412331317095
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of a DMAGaS/DMAAS mixed crystal

Abstract: Dimethylammonium gallium sulphate hexahydrate (DMAGaS) and dimethylammonium aluminum sulphate hexahydrate (DMAAS) are isomorphous and ferroelastic at room temperature. They both show an orderdisorder type transition into a ferroelectric phase, but only DMAGaS exhibits a further first-order transition into a low-temperature nonferroelectric phase. In this article, the results of dielectric measurements of the mixed crystal (DMAGaS) 0.9 (DMAAS) 0.1 are presented. It has been found that the phase transition tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Dielectric measurements of the mixed crystal (DMAGaS) 0.9 (DMAAS) 0.1 have been performed in the frequency range from 10 Hz to 1 MHz [25]. Figure 8 presents the temperature dependences of the real and imaginary parts of the dielectric permittivity for five selected frequencies, 100 Hz, 1 kHz, 10 kHz, 100 kHz and 1 MHz.…”
Section: Dielectric Measurements 221 the Solid Solution (Chmentioning
confidence: 99%
See 1 more Smart Citation
“…Dielectric measurements of the mixed crystal (DMAGaS) 0.9 (DMAAS) 0.1 have been performed in the frequency range from 10 Hz to 1 MHz [25]. Figure 8 presents the temperature dependences of the real and imaginary parts of the dielectric permittivity for five selected frequencies, 100 Hz, 1 kHz, 10 kHz, 100 kHz and 1 MHz.…”
Section: Dielectric Measurements 221 the Solid Solution (Chmentioning
confidence: 99%
“…It was shown that under high hydrostatic pressure the ferroelectric phase of DMAGaS disappears whereas in DMAAS new phases of unknown character appear between paraelectric and ferroelectric phases. Last but not least, it was shown very recently that an admixture of 10% DMAAS into a DMAGaS crystal leads to a remarkable decrease of the transition temperature from the ferroelectric to the modulated phase but to almost no change of the paraelectric-ferroelectric transition temperature T C1 [25].…”
Section: Introductionmentioning
confidence: 99%